2021
DOI: 10.1016/j.cub.2021.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Ancient genomes reveal structural shifts after the arrival of Steppe-related ancestry in the Italian Peninsula

Abstract: Ancient genomes reveal structural shifts after the arrival of Steppe-related ancestry in the Italian Peninsula Highlights d 22 genomes from Northeastern and Central Italy dated between 3200 and 1500 BCE d Arrival of Steppe-related ancestry in the central Italian Peninsula by 1600 BCE d Close patrilineal kinship patterns within commingled Chalcolithic cave burials d Roman Imperial period had a stronger effect on phenotype shifts than the Bronze Age

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
83
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 48 publications
(89 citation statements)
references
References 126 publications
5
83
0
1
Order By: Relevance
“…However, with the increase of ancient samples examined, subtle differences between Central-West and Central-East Europe started to emerge, with samples from Western and Eastern Europe forming two distinct clusters in the PCA (Fig. 2C) (Olalde et al 2015;Rivollat et al 2020;Marcus et al 2020;Saupe et al 2021). F4 statistics and related method (qpAdm) showed that this separation is possibly due to different amounts of ancestry related to WHG.…”
Section: Neolithic and Copper Agementioning
confidence: 97%
“…However, with the increase of ancient samples examined, subtle differences between Central-West and Central-East Europe started to emerge, with samples from Western and Eastern Europe forming two distinct clusters in the PCA (Fig. 2C) (Olalde et al 2015;Rivollat et al 2020;Marcus et al 2020;Saupe et al 2021). F4 statistics and related method (qpAdm) showed that this separation is possibly due to different amounts of ancestry related to WHG.…”
Section: Neolithic and Copper Agementioning
confidence: 97%
“…This could possibly depend on the small sample size of the available ancient populations, combined with the relatively low quality of genotype and sequence data, not having enough power to recover the subtle differences between the two Neolithic founder populations. However, with the increase of ancient samples examined, subtle differences between Central-West and Central-East Europe started to emerge, with samples from Western and Eastern Europe forming two distinct clusters in Principal Component Analyses (PCA, Figure 2C) [11,28,30,31]. F4 statistics and related methods (qpAdm) showed that this separation is possibly due to different amounts of ancestry related to WHG.…”
Section: Neolithic and Copper Agementioning
confidence: 99%
“…Also Sardinia and Sicily received this ancestry through the expansion of the Bell Beaker complex after ~4,459 ya [12,39]. More specifically, the timing of the Steppe-related ancestry arrival in Italy was a central topic of a recent study, examining human remains from Northeastern and Central Italy dated to the Chalcolithic and Bronze Age [31]. As a confirmation of other Central European studies [37], they found a gradual increase in such ancestry over time, with the first appearance in Early Bronze Age Italians (Italian Bell Beaker ~4,000 ya [37], Italian Remedello ~3,900 ya [33], and Grottina dei Covoloni del Broion dated ~3,800 [31].…”
Section: Bronze Agementioning
confidence: 99%
See 2 more Smart Citations